Pengaruh Citra Merek terhadap Niat Beli Konsumen (Studi pada Toyota Agya) - Jeremi Francis Setiadi; Tommy Setiawan Ruslim (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
The purpose of this study is to determine whether 1) brand image significantly influences the consumer price of Toyota Agya cars. 2) brand image significantly influences the perceived quality of consumers of Toyota Agya cars. 3) perceived price significantly influences the purchase intention of Toyota Agya car consumers. 4) perceived quality significantly influences the purchase intention of Toyota Agya car consumers. 5) brand image significantly influences the purchase intention of Toyota Agya car consumers mediated by perceived price. 6) brand image significantly influences the purchase intention of Toyota Agya car consumers mediated by perceived quality. Sample was selected by convenience sampling method with a total of 100 samples. And the results of this study indicate that the brand image has a positive and significant effect on the perceived price and perceived quality of Toyota Agya car consumers, the perceived price has a positive but not significant effect on the purchase intention of Toyota Agya car consumers, perceived quality has a positive and significant effect on the purchase intention of Toyota car consumers Agya, brand image has a positive but not significant effect on consumer purchase intentions mediated by perceived prices, and brand image has a positive and significant effect on consumer purchase intentions mediated by perceived qualityTujuan dari penelitian ini adalah untuk mengetahui apakah 1) Brand image berpengaruh secara signifikan terhadap perceived price konsumen mobil Toyota Agya. 2) Brand image berpengaruh secara signifikan terhadap perceived quality konsumen mobil Toyota Agya. 3) Perceived price berpengaruh secara signifikan terhadap purchase intention konsumen mobil Toyota Agya. 4) Perceived quality berpengaruh secara signifikan terhadap purchase intention konsumen mobil Toyota Agya. 5) Brand image berpengaruh secara signifikan terhadap purchase intention konsumen mobil Toyota Agya yang dimediasi oleh perceived price. 6) Brand image berpengaruh secara signifikan terhadap purchase intention konsumen mobil Toyota Agya yang dimediasi oleh perceived quality. Sampel dipilih dengan metode convenience sampling dengan jumlah sebanyak 100 sampel. Dan hasil penelitian ini menunjukkan bahwa brand image berpengaruh positif dan signifikan terhadap perceived price dan perceived quality konsumen mobil Toyota Agya, perceived price berpengaruh positif tetapi tidak signifikan terhadap purchase intention konsumen mobil Toyota Agya, perceived quality berpengaruh positif dan signifikan terhadap purchase intention konsumen mobil Toyota Agya, brand image berpengaruh positif tetapi tidak signifikan terhadap purchase intention konsumen yang dimediasi oleh perceived price, dan brand image berpengaruh positif dan signifikan terhadap purchase intention konsumen yang dimediasi oleh perceived quality